Hygienic assessment of occupational risk for workers during pre- and post-emergence herbicide treatments of sunflower crops - O.O. Novokhatska; M.V. Kondratiuk; A.M. Grynzovskyi; I.M. Pelo; V.V. Babiienko (Medičnì Perspektivi, 2024)
Modern agriculture extensively uses pesticide formulations at various stages of crop growth. Sunflower cultivation accounts for 31% of the global production. Assessing the occupational risk associated with pesticide application in sunflower farming is of paramount importance. Improper handling and application of pesticide formulations can have immediate adverse effects on workers, leading to acute poisoning, long-term health consequences, and the potential for chronic illnesses, including neurotoxic effects. The aim of this study was to conduct a hygienic assessment of the professional risk faced by workers during pre- and post-emergence herbicide applications in sunflower cultivation. This assessment was carried out to establish the regulations for their safe usage. Research samples after the application of the herbicides AGAT, GARPUN, KORVUS, and PARUS (patches from overalls, gloves, skin swabs from exposed areas (face-neck, hands), air samples (atmospheric air, working zone and drift zone). The assessment of professional risk was conducted in accordance with the methodological recommendations provided by experts from the L.I. Medved's Research Center of Preventive Toxicology, Food and Chemical Safety, Ministry of Health, Ukraine (State Enterprise). Statistical analysis of the results was carried out using the licensed statistical software packages MedStat v.5.2 (Copyright© 2003-2019) and Microsoft® Excel® for Microsoft 365 MSO (Version 2305, Build 16.0.16501.20074). It has been determined that under real conditions, during pre- and post-emergence herbicide applications in sunflower cultivation using AGAT, GARPUN, KORVUS, PARUS preparations, while adhering to recommended agrotechnical and hygiene safety regulations, the inhalation, dermal, complex, and combined (AGAT and PARUS) risks for applicators are 0.0409±0.0179, 0.0429±0.0193, 0.0838±0.0224, and 0.1557±0.1322 a.u., respectively, and for tractor operators – 0.0818±0.0358, 0.0425±0.0192, 0.1243±0.0356, and 0.2347±0.1567 a.u., respectively. There is no observed increase in hygiene standards in the workplace atmosphere and in the air of the potential drift zone. It has been proven that the professional risk of their use does not exceed permissible limits (<1). It has been determined that during the performance of technological operations, the mentioned risks in applicators and tractor operators did not differ significantly (p>0.05). However, a significant difference was found in the proportion of percutaneous risk (42.7±17.4% in applicators compared to 34.8±17.0% in tractor operators; p=0.034). The regulations for the safe use of the investigated pesticide formulations have been substantiated. Statistical analysis of the obtained results revealed that the values of inhalation, dermal, and combined risks during the application of these pesticides did not significantly differ during the various technological operations (applicators and tractor operators) (p>0.05). The values of the combined comprehensive risk associated with the use of the studied preparations also did not show significant differences (p>0.05). The proportion of dermal risk was significantly higher in applicators compared to this parameter determined in tractor operators (p=0.034).